Cardiogenic shock: current epidemiology and management. Issue 3 (9th October 2017) - Kataja, A.; Harjola, V.‐P.
Abstract: Cardiogenic shock (CS) is the most severe form of acute heart failure, characterized by low cardiac output, hypotension, and systemic hypoperfusion. CS is the leading cause of death in acute coronary syndrome (ACS) that accounts for about 80% of CS cases. In addition to acute cardiac cause, the diagnostic criteria for CS include persistent hypotension (systolic blood pressure < 90 mmHg) and clinical signs of hypoperfusion. Mortality rates in CS remain as high as 35–50%. Severe left ventricular dysfunction usually triggers the shock and leads to the activation of systemic inflammatory response and hypothalamic‐pituitary‐adrenal axis. Immediately after detection of the shock, electrocardiography and echocardiography should be performed to determine the etiology of CS and to rule out mechanical complications. Urgent revascularization by percutaneous coronary intervention, or less often by coronary artery bypass graft, is the most important treatment in CS caused by ACS. In the case of mechanical complication, immediate surgical treatment is essential. Regardless of the etiology, the basic treatment strategy includes fluid challenge that aims at obtaining euvolemia and relieving tissue hypoperfusion. Inotropes and vasopressors are often needed to improve cardiac performance and to maintain sufficient blood pressure. Ventilation is often supported mechanically and CS patients are best treated in intensive cardiac care unit. Continuous invasive blood pressure monitoring, electrocardiography, and repeated echocardiography are required. In CS refractory to other treatments, mechanical circulatory support may be considered to maintain adequate perfusion pressure and to prevent multiorgan failure. Answer questions and earn CME: https://wileyhealthlearning.com/Activity2/5608947/Activity.aspx